Design and construct a bioreactor for retinal pigment epithelium (RPE) tissue engineering - Neo, Chin Ding (2015)
The purpose of the report is to design and fabricate a bioreactor for retinal pigment epithelium (RPE) tissue engineering purposes by additive manufacturing. Bioreactor for tissue engineering purposes provides an in vitro environment which support cell proliferation. In this study, a fully functional circuit of perfusion bioreactor was established by connecting a pump, a media reservoir and a flow chamber where cell scaffold is anchored. The flow chamber inside the circuit was designed by SolidWorks. In order to optimize the design in terms of fluid flow, Computational fluid dynamics (CFD) models were used to estimate the flow fields and velocity profiles along the chamber. Second design was found to have more uniform velocity distribution inside the cell culturing region. Furthermore, an inlet velocity of 0.7m/s provides a fluid flow range from 0.03m/s to 0.06m/s inside the cell culturing region which is near to the velocity of the blood capillaries supplying nutrients to the RPE cells. This design was then being constructed by using ProJet 5500X printer. The model printed was accurate and proven to be functional as a flow chamber. The writer provides an initial check of the functionality of the perfusion bioreactor by pumping colored water through the circuit. The writer has successfully proven that the flow chamber fabricated by additive manufacturing technology is functional and can be used for tissue engineering purposes.